Study on the Structural Characteristics and Foaming Properties of Ovalbumin—Citrus Pectin Conjugates Prepared by the Maillard Reaction - Shanshan Zhang; Yibo Liu; Wenhui Wu (Foods)
This study explored the structural features and foaming properties of ovalbumin (OVA) and its glycosylated conjugates with citrus pectin (CP) formed through the Maillard reaction. The results demonstrated that OVA and CP were successfully conjugated, with the degree of grafting increasing to 43.83% by day 5 of the reaction. SDS-PAGE analysis confirmed the formation of high-molecular-weight conjugates. Fourier-transform infrared (FT-IR) and fluorescence spectroscopy further revealed alterations in the secondary and tertiary structures of OVA, including an enhanced β-sheet content, a reduced β-turn content, and the depletion of tryptophan residues. Moreover, the surface hydrophobicity of the OVA–CP conjugates significantly increased, enhancing foaming properties. Furthermore, the analysis of foaming properties exhibited that the Maillard reaction improved the foaming capacity of OVA to 66.22% and foaming stability to 81.49%. These findings highlight the potential of glycosylation via the Maillard reaction to significantly improve the foaming properties of OVA, positioning it as a promising novel foaming agent.